The cosmopolitan ideal: challenges and opportunities - O'Byrne, Darren J. (Rowman & Littlefield International, 2015)
Contents; Introduction; I: The Debate on Cosmopolitanism and Connected Discourses; Chapter One: Humanity, Rights, and the Ideal of a Global Critical Cosmopolitanism; Chapter Two: A Feminist Cosmopolitanism; II: The Challenges of Intercultural Communication; Chapter Three: Finding the Universality beyond Language and Culture; Chapter Four: Back to the Future; Chapter Five: Writing-Through a Critical Cosmopolitan Lens; Chapter Six: A New Cosmopolitan World History?; III: The Challenges of Pluralism and Difference; Chapter Seven: The Cosmopolitan Ideal and the Civilizing Process
Description based upon print version of record
Gesehen am 22.10.2015
Keywords: Electronic books